2012
DOI: 10.1159/000186926
|View full text |Cite
|
Sign up to set email alerts
|

The Anx7(+/-) Knockout Mutation Alters Electrical and Secretory Responses to Ca2+-Mobilizing Agents in Pancreatic �-cells

Abstract: Insulin secretion from the pancreatic β-cell is controlled by changes in membrane potential and intracellular Ca2+. The contribution of intracellular Ca2+ stores to this process is poorly understood. We have previously shown that β-cells of mice lacking one copy of the Annexin 7 gene (Anx7(+/-)) express reduced levels of IP3 receptors and defects in IP3-dependent Ca2+ signaling. To further elucidate the effect of the Anx7(+/-) mutation on signaling related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Furthermore, knockout mouse is not an ideal model for ANXA7 research in disease, because homozygous ANXA7 ( −/− ) mutation is lethal by E10, 16 and ANXA7( +/− ) mutation also has several unwished phenotypes, such as induce β -cell hypertrophy, islet hyperplasia, an alteration in the Ca 2+ dependence of glucose-induced insulin secretion, and aberrant regulation of islet gene expression by the fed/fasted state. 17 Fortunately, in a recent study, we found that ABO could directly bind to ANXA7 and inhibit phosphorylation of ANXA7, 18 which had a significant inhibitory effect on its GTPase activity. 19 Our findings suggest that as a small molecule modulator of ANXA7 function, ABO is a powerful tool to study the complex cellular functions of ANXA7.…”
mentioning
confidence: 87%
“…Furthermore, knockout mouse is not an ideal model for ANXA7 research in disease, because homozygous ANXA7 ( −/− ) mutation is lethal by E10, 16 and ANXA7( +/− ) mutation also has several unwished phenotypes, such as induce β -cell hypertrophy, islet hyperplasia, an alteration in the Ca 2+ dependence of glucose-induced insulin secretion, and aberrant regulation of islet gene expression by the fed/fasted state. 17 Fortunately, in a recent study, we found that ABO could directly bind to ANXA7 and inhibit phosphorylation of ANXA7, 18 which had a significant inhibitory effect on its GTPase activity. 19 Our findings suggest that as a small molecule modulator of ANXA7 function, ABO is a powerful tool to study the complex cellular functions of ANXA7.…”
mentioning
confidence: 87%
“…Consequently, anomalous Ca 2+ release from intracellular stores, causing defects in Ca 2+ signal transduction that drive insulin secretion in pancreatic β-cells, was observed. Follow-up studies identified that abnormal insulin secretion in β-cells from AnxA7 +/-mice gene was further compromised by a change in the sensitivity to activate ryanodine receptor (RyR) -mediated Ca 2+ release (Mears et al, 2012) (Table 7). In line with the tumor suppressor activity of AnxA7, the heterozygous Anx7 +/-strain also revealed a cancerprone phenotype, with more than 20% of the mutant mice developing spontaneous neoplasms (Srivastava et al, 2003).…”
Section: Anxa7 Ko Micementioning
confidence: 99%
“…As pointed out by the authors, this does not rule out other mechanisms. Thus, altered RyR receptor signaling in pancreatic β-cells observed in the heterozygous AnxA7 +/-model as underlying cause for enhanced glucose-stimulated insulin secretion should also be considered (Mears et al, 2012). Taking into account the complex involvement of COX enzymes in inflammatory and other diseases, and the wide expression of IP 3 and RyR receptors affecting cellular signaling and Ca 2+ homeostasis in numerous cells, future studies will have to clarify the contribution of the various candidates affected by AnxA7 deficiency, including COX, IP 3 or RyR receptors.…”
Section: Anxa7 Ko Micementioning
confidence: 99%
“…ANXA7 was reported to be a tumor suppressor and participated in tumorigenesis through a signaling pathway engaging other tumor suppressor genes, DNA-repair genes, senescence and apoptosisrelated genes (Kriebardis et al, 2007;Srivastava et al, 2001Srivastava et al, , 2003. Previous studies showed that homozygous ANXA7(−/−) mutation is lethal by E10 (Herr et al, 2001), and ANXA7(+/−) mutation also has several unpredicted phenotypes, such as induction of islet hyperplasia, ␤-cell hypertrophy, abnormal regulation of islet gene expression by the fed/fasted state, and an alteration in the Ca 2+ -dependence of glucose-induced insulin secretion (Mears et al, 2012). Therefore, traditional genetic method is very difficult for determining the role of ANXA7 GTPase in cell signaling.…”
Section: Introductionmentioning
confidence: 99%